New Mexico and the Pimería Alta : The Colonial Period in the American Southwest - Graves, William M.; Douglass, John G., 1968- (Book collections on Project MUSE., 2017)
"Focusing on two areas of the Southwest that witnessed intensive and sustained colonial encounters and compares how different forms of colonialism and indigenous political economies structured the outcomes of those encounters. A holistic approach studying both colonist and indigenous perspectives through archaeological, ethnohistoric, historic, and landscape data"--Provided by publisher.